Development, Validation, and Reliability Testing of the Brief Instrument to Assess Workers› Productivity during a Working Day (IAPT) - De Menezes, Fabio Sprada; Xavier, Antonio Augusto de Paula (Review of Business Management, 2018)
Purpose – The aim of this study was to develop, validate, and test the clarity and reliability of the Brief Instrument to Assess Workers’ Productivity during a Working Day. Design/methodology/approach –The content of the instrument was chosen using research containing other valid instruments and after this the construct was developed. Relevance and clarity validations were conducted with experts using Likert scales (from 0 to 10), convergent validity was performed using the Health and Productivity Questionnaire (HPQ) and Health & Labor Questionnaire (HLQ) instruments, and reliability measures were carried out using the Split Half Test and Cronbach’s Alpha coefficient. Findings – The instrument proved to be clear and relevant with an average of 9.11±0.93 in the relevance test and 9.23±0.75 in the clarity test. Regarding convergent validity, the instrument showed a high correlation with the HPQ (r2 = 0.86) and the HLQ (r2 = 0.82). The reliability results were r2 = 0.78 in the Split Half Test and a Cronbach’s Alpha coefficient of α = 0.91 for the Management variables and α = 0.80 for the Physical and Mental Variables. Originality/value – The proposed instrument was shown to have an adequate content and construct, in addition to converging results with other recognized instruments, and it had very high levels of reliability. All these factors define it as a good tool for research regarding productivity in companies.